Evaluation Report on Working of Community Projects and N.E.S. Blocks Summary April 1957 - Planning Commission (Planning Commission, 1937)
The Evaluation Report on the Working of Community Projects and National Extension Service (N.E.S.) Blocks, published in April 1957, assesses the transition from intensive community development projects to the post-intensive phase in rural India. The report identifies significant challenges arising from abrupt shifts in funding patterns, reduced emphasis on extension work, and the absence of medium-term agricultural credit. While notable achievements were made in infrastructure development and irrigation, progress in cottage industries, social transformation, and community self-reliance remained uneven. Administrative shortcomings, including weak coordination and inadequate staff orientation, further constrained outcomes. The report recommends improved transition planning, restoration of medium-term loans, strengthened community engagement, enhanced staff training, and equitable distribution of resources to ensure sustainable and participatory rural development.
Summary of Conclusions and Recommendations
Programme Evaluation Organisation Planning Commission
Keywords: Community Development Programmes; National Extension Service Blocks; Post-Intensive Phase; Rural Development Planning; Agricultural Credit; Community Participation; Administrative Coordination; Capacity Building; Equitable Resource Distribution; Rural Infrastructure; Extension Services; Planning Transition